Kearifan Lokal Madura Rokat Bhuju’ Siti Rohana sebagai Alternatif Muatan Lokal Era Merdeka Belajar - Moh. Hafid Effendy; Maulidiawati Maulidiawati; Agus Purnomo Ahmad Putikadyanto (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2022)
This research examines and describes the existence of the local wisdom of Madura rokat bhuju' Siti Rohana as an alternative to local content in the era of independent learning. The focus of the research reveals 1) the manifestation of the existence of local wisdom of the Madurese people of Rokat Bhuju' Siti Rohana, 2) the procession of the existence of local wisdom of the Madurese people of Rokat Bhuju' Siti Rohana, and 3) the message contained in Rokat Bhuju' Siti Rohana. This research uses a qualitative approach with a descriptive type. Data collection techniques were carried out by means of interviews, observation, and documentation. The results of the study show that: 1) The manifestation of the existence of the local wisdom of Rokat Bhuju' is in the form of continuing to carry out traditional ceremonies and giving tambul (bu'-sobu') or food. 2) The Bhuju Rokat procession was initially carried out by slaughtering a plain white chicken by the caretaker, the community prepared skol rice, kocor snack cakes, and grilled chicken. After the community has gathered, the rokat procession begins with the reading of Yasin's letter, Tahlil, prayer, and ends with the exchange of snacks between the communities brought to the event. 3) ordered rokat bhuju' to keep away from disasters, and the economy of the surrounding community improves smoothly. The positive values contained in Siti Rohana's bhuju' rokat can be used as local content for typical Madurese learning.